دراسة مقارنة لتأثير الأشعة فوق البنفسجية (UV-B) في أصبغة التركيب الضوئي عند نوعين من البكتيريا الخضـراء المزرقة Anabaena variabilis و Nostoc muscorum - عياش عبد الكريم; ميهوب حامد; ديــــوب عبيــر (Latakia University Journal -Biological Sciences Series, 2019)
تم في هذه الدراسة استزراع نوعين من البكتيريا الخضراء المزرقة مخبرياً وهما النوستوك Nostoc muscorum والأنابينا Anabaena variabilis، ومن ثم دراسة تأثير الأشعة فوق البنفسجية (UV-B) عند طول الموجة (285nm) القريبة من الأشعة فوق البنفســــــجية (UV-C) ولفترات زمنية قصيرة (5 ـــ 20 دقيقة) في أصبغة التركيب الضوئي لدى هذين النوعين. لوحظ ازدياد في تركيز الكاروتينويدات في خلايا كلا نوعي البكتيريا، إلا أن هذه الزيادة كانت بعد 20 دقيقة أشد عند بكتيريا الأنابينا مقارنة بالنوستوك (113% ، 52 % على التوالي). بينما لوحظ انخفاض في تركيز اليخضور (أ) بعد خمس دقائق عند كلا نوعي البكتيريا، لكنه كان أكثر وضوحاً عند بكتيريا الأنابينا منه عند بكتيريا النوستوك ( 45%، 33% على التوالي). إن مقاومة النوستوك مقارنة بالأنابينا لنمط الأشعة المدروسة يمكن أن يعزى إلى وجود غلاف مخاطي سميك يحيط بالخلايا إضافة إلى الصبغات الكاروتينويدية، بينما تقوم هذه الصبغات منفردة بالحد من تأثير هذه الأشعة في خلايا الأنابينا بسبب قلة سماكة الغلاف المخاطي. In this study, two species of cyanobacteria (Nostoc muscorum and Anabaena variabilis) have been cultivated in the laboratory, and then studied for the effect of ultraviolet radiation (UV-B) at the wavelength (285nm) near ultraviolet radiation (UV-C) for short periods (5 - 20 minutes) on the photosynthetic pigments in both species . Results showed increasing the concentration of carotenoids in the cells of both species, but this increase after 20 minutes was more significant in Anabaena compared to Nostoc (113%, 52%, respectively). While there was a decrease in the concentration of chlorophyll a after five minutes in both species of bacteria, but it was more pronounced in Anabaena than in Nostoc (45%, 33%, respectively). The resistance of Nostoc compared to Anabaena to the studied rays can be attributed to the existence of a mucous sheath surrounding the cells in addition to carotenoid pigments, while this pigments alone in Anabaena reduce the effect of this radiations on the cells, because of the absence of the mucous sheath.